Polyethylene flame-retardant fiber and preparation method thereof
By preparing alumina composite and combining it with phosphorus oxychloride and epoxidized guar gum, functional flame retardant composites are formed, which solves the problems of poor long-term flame retardant, poor water-washing resistance and ultraviolet radiation resistance, and significantly improves the flame retardant and service life of the fiber.
Patent Information
- Application Number
- CN202411884440.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polyethylene flame retardant fibers have poor long-term flame retardant properties, poor washing resistance and ultraviolet radiation resistance, resulting in a shortening of the service life of the fiber.
Alumina composites are prepared by specific methods, and functional flame retardant composites are formed by combining with phosphorus oxychloride and epoxidized guar gum to improve the flame retardant and compatibility of the fibers.
The flame retardancy, strength and stability of polyethylene fibers are improved, and the washing resistance and UV radiation resistance are significantly improved, and the service life of the fibers is also extended accordingly.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyethylene fibers, and in particular relates to a polyethylene flame-retardant fiber and a preparation method thereof. Background Art
[0002] Polyethylene fiber is a fiber material obtained by melt spinning polyethylene, also known as vinyl fiber. Polyethylene fiber has the advantages of high strength, low density, good insulation and good corrosion resistance. It is widely used in military industry, marine industry, aerospace, safety protection, sports industry and other fields.
[0003] However, since the molecular chain of polyethylene fiber is mainly composed of C and H, it has high flammability and a very low limiting oxygen index. The heat and smoke generated during the combustion process are very large, and molten droplets may occur, causing secondary disasters. Therefore, providing a polyethylene flame-retardant fiber and a preparation method thereof has become a research and development topic for technicians.
[0004] In the process of preparing polyethylene flame-retardant fiber, flame retardants are usually added to the fiber raw materials or flame retardant coatings are applied to the surface of the formed fibers. However, this will affect the mechanical properties of the fibers. In addition, due to the high orientation and high crystallinity of polyethylene fibers, the macromolecules have no polar groups and their surface energy is low, which greatly affects the interfacial bonding properties with the flame retardant. During the use or washing of polyethylene fibers, they are easy to fall off and pollute the environment.
[0005] In this regard, a large number of microcapsule-type flame retardants have appeared on the market. Mixing them with polyethylene and then melt-extruding them can effectively improve the flame retardant properties of polyethylene fibers. For example, CN114086272A discloses an antibacterial flame-retardant ultra-high molecular weight polyethylene fiber and a preparation method thereof, which specifically discloses that a mixture of ultra-high molecular weight polyethylene, high-density polyethylene, low molecular weight polypropylene, modified nano-additives, antioxidant 1010, antioxidant 168, antibacterial agent, microcapsule flame retardant, lubricant and compatibilizer is extruded through a twin-screw, melted and mixed, conveyed, sheared, and melt-spun to obtain antibacterial flame-retardant ultra-high molecular weight polyethylene; the preparation method of the microcapsule flame retardant is to add cerium carbonate, polyacrylic acid amide, and urea to deionized water in turn and stir evenly, then add a flame retardant core and mix and stir, and disperse to obtain a cerium-coated microcapsule flame retardant; The polyethylene flame-retardant fiber prepared by this method has good material compatibility, and the microcapsule flame retardant can reduce the amount of flame retardant while ensuring the flame retardant effect. However, the flame retardant effect of the fiber prepared by this method is still poor, and the creep resistance is poor.
[0006] After searching, the applicant found that the polyethylene flame-retardant fibers prepared by the prior art all have the problem of poor long-term flame retardancy. After multiple washings, the flame retardant effect of the polyethylene fibers is significantly reduced, and the prepared polyethylene flame-retardant fibers have poor resistance to ultraviolet radiation. Long-term ultraviolet radiation causes their strength performance to decrease significantly, seriously shortening the service life of the fibers. Summary of the invention
[0007] In order to solve the technical problems existing in the prior art, the present invention provides a polyethylene flame retardant fiber and a preparation method thereof, the fiber has high strength, good flame retardancy, good creep resistance, excellent water washability and ultraviolet radiation resistance.
[0008] In view of the above technical problems, the present invention adopts the following technical solutions: A method for preparing polyethylene flame-retardant fiber includes preparing an aluminum oxide composite, preparing a primary flame-retardant composite, preparing a functional flame-retardant composite, and mixing steps, which are specifically as follows: 1. Preparation of Alumina Composites Place alumina in a muffle furnace, heat it to 316-327°C at a rate of 5.5-6.5°C / min, and calcine it at this temperature for 3.8-4.2 hours. After calcination, wait for it to naturally cool to room temperature, put it into an ethanol solution, add polyvinyl pyrrolidone, raise the temperature to 38-42°C and stir for 27-33 minutes. After stirring, add vinyl tri(β-methoxyethoxy) silane and vinyl trimethoxy silane, heat it to 65-70°C at a rate of 1.4-1.6°C / min, and stir for 4 .8-5.2h, after the end of heat preservation and stirring, filter and wash, then add to N, N-dimethylformamide, add 4-mercaptoaniline, stir evenly, add benzoin dimethyl ether for ultrasonic dispersion, the ultrasonic time is 24-26min, the ultrasonic power is 115-124W, the ultrasonic frequency is 30-34kHz, after the end of ultrasonic dispersion, carry out ultraviolet irradiation, the irradiation time is 1.4-1.6h, the ultraviolet wavelength is 253-264nm, after the end of irradiation, filter, wash and dry to obtain an aluminum oxide composite; The mass ratio of the aluminum oxide, ethanol solution, polyvinyl pyrrolidone, vinyl tri(β-methoxyethoxy) silane, vinyl trimethoxy silane, N,N-dimethylformamide, 4-mercaptoaniline, and benzoin dimethyl ether is 15.5-16.0:117-123:1.4-1.6:0.8-1.2:0.5-0.7:490-510:17.7-18.0:1.5-1.7; The mass concentration of the ethanol solution is 28-31%.
[0009] 2. Preparation of primary flame retardant composites Put phosphorus oxychloride in dichloroethane, stir evenly to prepare a flame retardant liquid; put the aluminum oxide complex in dichloroethane, stir evenly, then drop the flame retardant liquid, control the drop rate to 0.4-0.6g / min, after the drop is completed, raise the temperature to 54-58°C, keep stirring for 4.8-5.2h, cool to room temperature, filter, wash and dry to obtain a primary flame retardant complex; The mass ratio of phosphorus oxychloride to ethylene dichloride is 7.7-7.7:95-105; The mass ratio of the aluminum oxide complex, ethylene dichloride and flame retardant liquid is 5.4-5.8:245-255:19.6-20.5.
[0010] 3. Preparation of functional flame retardant composites The primary flame retardant composite is placed in an ethanol solution, chitosan is added and stirred, after stirring evenly, epoxidized guar gum is added, the temperature is raised to 50-54°C, and the reaction is stirred at 196-205 rpm for 4.8-5.2 hours. After the reaction is completed, the composite is filtered and washed, and freeze-dried at a freezing temperature of -30 to -26°C for 11.6-12.4 hours. The composite is then naturally restored to room temperature to obtain a functional flame retardant composite. The mass ratio of the primary flame retardant composite, ethanol solution, chitosan and epoxidized polyester is 6.1-6.4:195-205:1.6-2.0:2.2-2.5; The mass concentration of the ethanol solution is 58-62%; The preparation method of the epoxidized guar gum comprises the following steps: placing the guar gum in an ethanol solution, stirring evenly, adding sodium alginate and γ-glycidyloxypropyltriethoxysilane, raising the temperature to 60-64° C., keeping the temperature and stirring for 3.4-3.6 hours, filtering, washing and drying after the stirring is completed, so as to obtain the epoxidized guar gum; The mass ratio of the guar gum, ethanol solution, sodium alginate and γ-glycidyloxypropyltriethoxysilane is 3.3-3.7:48-52:1.0-1.2:0.4-0.6; The mass concentration of the ethanol solution is 32-38%.
[0011] 4. Mixing Ultra-high molecular weight polyethylene, medium molecular weight polyethylene, low molecular weight polyethylene, functional flame retardant compound, antioxidant 1010, oxidized polyethylene wax, oleic acid amide and sodium dodecylbenzene sulfonate are mixed, the stirring speed is 864-875rpm, the stirring time is 18-22min, after the stirring, it is put into a twin-screw extruder for melt spinning, the spinning temperature is 248-252℃, and then three-stage drawing is carried out, the first-stage drawing temperature is 98-103℃, the drawing ratio is 4.7-5.3 times, the second-stage drawing temperature is 115-120℃, the drawing ratio is 3.8-4.2 times, the third-stage drawing temperature is 125-130℃, and the drawing ratio is 2.4-2.6 times, to obtain polyethylene flame retardant fiber; The mass ratio of the ultra-high molecular weight polyethylene, medium molecular weight polyethylene, low molecular weight polyethylene, functional flame retardant compound, antioxidant 1010, oxidized polyethylene wax, oleic acid amide and sodium dodecylbenzene sulfonate is 15.8-16.2:58.7-60.5:12.6-13.4:3.6-4.0:1.0-1.4:0.8-1.2:0.7-1.3:0.5-0.8; The viscosity average molecular weight of the ultra-high molecular weight polyethylene is 2.24-2.26 million, the viscosity average molecular weight of the medium molecular weight polyethylene is 255,000-260,000, and the viscosity average molecular weight of the low molecular weight polyethylene is 5700-5900.
[0012] A polyethylene flame-retardant fiber is prepared by the above-mentioned preparation method.
[0013] Compared with the prior art, the present invention has achieved the following beneficial effects: 1. The present invention adopts a specific method to prepare an alumina composite, wherein alumina is used as a matrix, alumina is vinyl-modified, and its surface is rich in vinyl groups, and then a thiol group is introduced to carry out a thiol-ene chemical reaction, and an amino group is introduced into the alumina composite, thereby enhancing the compatibility of alumina and polyethylene and the loading performance of the flame retardant, so that the alumina has good dispersibility in the polyethylene matrix, and then phosphorus oxychloride is used as a flame retardant, so that the phosphorus oxychloride is combined with the amino group in the alumina composite, thereby improving the loading stability of the alumina composite for the flame retardant, and then The primary flame retardant compound is functionalized, and an epoxidized group is introduced on its surface, which can undergo a cross-linking reaction with the amino group of the alumina compound and the amino group of chitosan, so that the functional flame retardant compound presents a stable network structure, and the alumina has high thermal conductivity, heat dissipation and flame retardancy, and synergistically enhances the flame retardancy with the flame retardant, has good stability, and still has good flame retardancy after multiple washings, and the functional flame retardant compound has good compatibility with polyethylene, can be evenly dispersed in the polyethylene matrix, improves the strength and stability of the polyethylene fiber, and can still maintain high strength performance under ultraviolet radiation; 2. The polyethylene flame retardant fiber prepared by the present invention has a limiting oxygen index of 39.4-39.7%, and a limiting oxygen index of 38.1-38.8% after being washed 50 times; 3. The polyethylene flame retardant fiber prepared by the present invention has a tensile strength of 38.1-38.6 cN / dtex, an elongation at break of 5.8-6.2%, and a tensile modulus of 1288-1295 cN / dtex; 3. The polyethylene flame-retardant fiber prepared by the present invention has a creep elongation of 0.74-0.79% / h at 70°C and a load of 600MPa; 4. The polyethylene flame retardant fiber prepared by the present invention has a strength of 650W / cm 2 After irradiation under ultraviolet light for 21 days, the tensile strength is 36.8-37.8 cN / dtex and the tensile modulus is 1234-1257 cN / dtex. DETAILED DESCRIPTION
[0014] In order to more clearly understand the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described.
[0015] Example 1 1. Preparation of Alumina Composites 15.7g of alumina was placed in a muffle furnace, heated to 320℃ at a rate of 6.0℃ / min, and calcined for 4.0h. After calcination, it was naturally cooled to room temperature and put into 120g of 30wt% ethanol solution. 1.5g of polyvinyl pyrrolidone was added, and the temperature was raised to 40℃ for stirring for 30min. After stirring, 1.0g of vinyl tri(β-methoxyethoxy)silane and 0.6g of vinyl trimethoxysilane were added, and the temperature was raised to 68℃ at a rate of 1.5℃ / min. The mixture was stirred for 5.0h. After the stirring was completed, it was filtered and washed, and then added to 500g of N, N-dimethylformamide, and 17.9g 4-mercaptoaniline was stirred evenly, and then 1.6 g of benzoin dimethyl ether was added for ultrasonic dispersion. The ultrasonic time was 25 min, the ultrasonic power was 120 W, and the ultrasonic frequency was 32 kHz. After the ultrasonic dispersion was completed, ultraviolet light was irradiated for 1.5 h, and the ultraviolet wavelength was 260 nm. After the irradiation was completed, it was filtered, washed, and dried to obtain an aluminum oxide composite.
[0016] 2. Preparation of primary flame retardant composites Place 7.5g of phosphorus oxychloride in 100g of dichloroethane and stir evenly to obtain a flame retardant liquid; place 5.6g of alumina complex in 250g of dichloroethane and stir evenly, then drop 20.0g of flame retardant liquid, and control the drop rate to 0.5g / min. After the drop addition is completed, raise the temperature to 56°C, keep stirring for 5.0h, cool to room temperature, filter, wash and dry to obtain a primary flame retardant composite.
[0017] 3. Preparation of functional flame retardant composites 6.3 g of the primary flame retardant composite was placed in 200 g of a 60 wt% ethanol solution, 1.8 g of chitosan was added and stirred, and after stirring evenly, 2.4 g of epoxidized guar gum was added, the temperature was raised to 52° C., and the mixture was stirred at 200 rpm for 5.0 h. After the reaction was completed, the mixture was filtered and washed, and freeze-dried at a freezing temperature of -28° C. for 12.0 h, and then naturally recovered to room temperature to obtain a functional flame retardant composite. The preparation method of the epoxidized guar gum comprises the following steps: placing 3.5 g of guar gum in 50 g of a 35 wt % ethanol solution, stirring evenly, adding 1.1 g of sodium alginate and 0.5 g of γ-glycidyloxypropyltriethoxysilane, raising the temperature to 62° C., stirring at the temperature for 3.5 hours, filtering, washing and drying after the stirring is completed, so as to obtain the epoxidized guar gum.
[0018] 4. Mixing 16.0g ultra-high molecular weight polyethylene, 60.0g medium molecular weight polyethylene, 13.0g low molecular weight polyethylene, 3.8g functional flame retardant compound, 1.2g antioxidant 1010, 1.0g oxidized polyethylene wax, 1.0g oleic acid amide and 0.7g sodium dodecylbenzene sulfonate were mixed, the stirring speed was 870rpm, the stirring time was 20min, after the stirring, it was put into a twin-screw extruder for melt spinning, the spinning temperature was 250°C, and then three-stage drawing was carried out, the first-stage drawing temperature was 100°C, the drawing ratio was 5.0 times, the second-stage drawing temperature was 118°C, the drawing ratio was 4.0 times, the third-stage drawing temperature was 128°C, and the drawing ratio was 2.5 times, to obtain polyethylene flame retardant fiber; The viscosity average molecular weight of the ultra-high molecular weight polyethylene is 2.25 million, the viscosity average molecular weight of the medium molecular weight polyethylene is 257,000, and the viscosity average molecular weight of the low molecular weight polyethylene is 5,800.
[0019] Example 2 1. Preparation of Alumina Composites 15.5g of alumina was placed in a muffle furnace, heated to 316°C at a rate of 5.5°C / min, and calcined for 3.8h. After calcination, it was naturally cooled to room temperature and put into 117g of 28wt% ethanol solution. 1.4g of polyvinyl pyrrolidone was added, and the temperature was raised to 38°C for stirring for 27min. After stirring, 0.8g of vinyl tri(β-methoxyethoxy)silane and 0.5g of vinyl trimethoxysilane were added, and the temperature was raised to 65°C at a rate of 1.4°C / min. The mixture was stirred for 4.8h. After the stirring was completed, it was filtered and washed, and then added to 490g of N, N-dimethylformamide, and 17.7g 4-mercaptoaniline was stirred evenly, and then 1.5 g of benzoin dimethyl ether was added for ultrasonic dispersion. The ultrasonic time was 24 min, the ultrasonic power was 115 W, and the ultrasonic frequency was 30 kHz. After the ultrasonic dispersion was completed, ultraviolet light was irradiated for 1.4 h, and the ultraviolet wavelength was 253 nm. After the irradiation was completed, the aluminum oxide composite was obtained by filtration, washing, and drying.
[0020] 2. Preparation of primary flame retardant composites Place 7.3 g of phosphorus oxychloride in 95 g of dichloroethane and stir evenly to obtain a flame retardant liquid. Place 5.4 g of alumina complex in 245 g of dichloroethane and stir evenly, then drop 19.6 g of flame retardant liquid at a rate of 0.4 g / min. After the addition is completed, raise the temperature to 54°C, keep stirring for 4.8 hours, cool to room temperature, filter, wash, and dry to obtain a primary flame retardant composite.
[0021] 3. Preparation of functional flame retardant composites 6.1 g of the primary flame retardant composite was placed in 195 g of a 58 wt% ethanol solution, 1.6 g of chitosan was added and stirred, and after stirring evenly, 2.2 g of epoxidized guar gum was added, the temperature was raised to 50° C., and the reaction was stirred at 196 rpm for 4.8 h. After the reaction was completed, the composite was filtered and washed, and freeze-dried at a freezing temperature of -30° C. for 11.6 h. The composite was allowed to naturally return to room temperature to obtain a functional flame retardant composite. The preparation method of the epoxidized guar gum comprises the following steps: placing 3.3 g of guar gum in 48 g of 32 wt % ethanol solution, stirring evenly, adding 1.0 g of sodium alginate and 0.4 g of γ-glycidyloxypropyltriethoxysilane, raising the temperature to 60° C., keeping the temperature and stirring for 3.4 hours, filtering, washing and drying after the stirring is completed, so as to obtain the epoxidized guar gum.
[0022] 4. Mixing 15.8g ultra-high molecular weight polyethylene, 58.7g medium molecular weight polyethylene, 12.6g low molecular weight polyethylene, 3.6g functional flame retardant compound, 1.0g antioxidant 1010, 0.8g oxidized polyethylene wax, 0.7g oleic acid amide and 0.5g sodium dodecylbenzene sulfonate were mixed, the stirring speed was 864rpm, the stirring time was 18min, after the stirring, it was put into a twin-screw extruder for melt spinning, the spinning temperature was 248°C, and then three-stage drawing was carried out, the first-stage drawing temperature was 98°C, the drawing ratio was 4.7 times, the second-stage drawing temperature was 115°C, the drawing ratio was 3.8 times, the third-stage drawing temperature was 125°C, and the drawing ratio was 2.4 times, to obtain polyethylene flame retardant fiber; The viscosity average molecular weight of the ultra-high molecular weight polyethylene is 2.24 million, the viscosity average molecular weight of the medium molecular weight polyethylene is 255,000, and the viscosity average molecular weight of the low molecular weight polyethylene is 5,700.
[0023] Example 3 1. Preparation of Alumina Composites 16.0g of alumina was placed in a muffle furnace, heated to 327°C at a rate of 6.5°C / min, and calcined for 4.2h. After calcination, it was naturally cooled to room temperature and put into 123g of 32wt% ethanol solution. 1.6g of polyvinyl pyrrolidone was added, and the temperature was raised to 42°C for stirring for 33min. After stirring, 1.2g of vinyl tri(β-methoxyethoxy)silane and 0.7g of vinyl trimethoxysilane were added, and the temperature was raised to 70°C at a rate of 1.6°C / min, and the mixture was stirred for 5.2h. After the stirring was completed, the mixture was filtered and washed, and then added to 510g of N, N-dimethylformamide, and 18.0g of 4-mercaptoaniline was stirred evenly, and then 1.7 g of benzoin dimethyl ether was added for ultrasonic dispersion. The ultrasonic time was 26 min, the ultrasonic power was 124 W, and the ultrasonic frequency was 34 kHz. After the ultrasonic dispersion was completed, ultraviolet light was irradiated for 1.6 h, and the ultraviolet wavelength was 264 nm. After the irradiation was completed, the aluminum oxide composite was obtained by filtration, washing, and drying.
[0024] 2. Preparation of primary flame retardant composites Place 7.7 g of phosphorus oxychloride in 105 g of dichloroethane and stir evenly to obtain a flame retardant liquid; place 5.8 g of alumina complex in 255 g of dichloroethane and stir evenly, then drop 20.5 g of flame retardant liquid, and control the drop rate to 0.6 g / min. After the drop addition is completed, raise the temperature to 58°C, keep stirring for 5.2 hours, cool to room temperature, filter, wash, and dry to obtain a primary flame retardant composite.
[0025] 3. Preparation of functional flame retardant composites 6.4 g of the primary flame retardant composite was placed in 205 g of a 62 wt% ethanol solution, 2.0 g of chitosan was added and stirred, and after stirring evenly, 2.5 g of epoxidized guar gum was added, the temperature was raised to 54° C., and the reaction was stirred at 205 rpm for 5.2 h. After the reaction was completed, the composite was filtered and washed, and freeze-dried at a freezing temperature of -26° C. for 12.4 h, and then naturally recovered to room temperature to obtain a functional flame retardant composite. The preparation method of the epoxidized guar gum comprises the following steps: placing 3.7 g of guar gum in 52 g of 38 wt % ethanol solution, stirring evenly, adding 1.2 g of sodium alginate and 0.6 g of γ-glycidyloxypropyltriethoxysilane, raising the temperature to 64° C., keeping the temperature and stirring for 3.6 hours, filtering, washing and drying after the stirring is completed, so as to obtain the epoxidized guar gum.
[0026] 4. Mixing 16.2g ultra-high molecular weight polyethylene, 60.5g medium molecular weight polyethylene, 13.4g low molecular weight polyethylene, 4.0g functional flame retardant compound, 1.4g antioxidant 1010, 1.2g oxidized polyethylene wax, 1.3g oleic acid amide and 0.8g sodium dodecylbenzene sulfonate were mixed, the stirring speed was 875rpm, the stirring time was 22min, after the stirring, it was put into a twin-screw extruder for melt spinning, the spinning temperature was 252°C, and then three-stage drawing was carried out, the first-stage drawing temperature was 103°C, the drawing ratio was 5.3 times, the second-stage drawing temperature was 120°C, the drawing ratio was 4.2 times, the third-stage drawing temperature was 130°C, and the drawing ratio was 2.6 times, to obtain polyethylene flame retardant fiber; The viscosity average molecular weight of the ultra-high molecular weight polyethylene is 2.26 million, the viscosity average molecular weight of the medium molecular weight polyethylene is 260,000, and the viscosity average molecular weight of the low molecular weight polyethylene is 5,900.
[0027] Comparative Example 1 Based on Example 1, the changes are as follows: The step of preparing the aluminum oxide composite is omitted, and in the process of preparing the primary flame retardant composite, the aluminum oxide composite is replaced by aluminum oxide without any treatment in equal amount; The rest of the operations are the same.
[0028] Comparative Example 2 Based on Example 1, the changes are as follows: The step of preparing the functional flame retardant compound is omitted; in the mixing step, the functional flame retardant compound is replaced by the primary flame retardant compound in equal amounts; The rest of the operations are the same.
[0029] Performance Testing The performance of the polyethylene flame retardant fibers obtained in Examples 1-3 and Comparative Examples 1-2 was tested as follows:
[0030] The invention adopts a specific method to prepare an alumina composite, wherein alumina is used as a matrix, vinyl-modified to the alumina so that its surface is rich in vinyl groups, and then thiol groups are introduced to carry out thiol-ene chemical reaction, thereby introducing amino groups on the alumina composite, thereby enhancing the compatibility of alumina and polyethylene and the loading performance of flame retardants, so that the alumina has good dispersibility in the polyethylene matrix, and then phosphorus oxychloride is used as a flame retardant, so that phosphorus oxychloride is combined with amino groups in the alumina composite, thereby improving the loading stability of the alumina composite for the flame retardant, and then the initial The flame retardant composite is functionalized by introducing epoxidized groups on its surface, which can undergo cross-linking reactions with the amino groups of the alumina composite and the amino groups of chitosan, so that the functional flame retardant composite presents a stable network structure. The alumina has high thermal conductivity, heat dissipation and flame retardancy, and synergizes with the flame retardant to enhance the flame retardancy and has good stability. It still has good flame retardancy after multiple washings. The functional flame retardant composite has good compatibility with polyethylene and can be evenly dispersed in the polyethylene matrix, thereby improving the strength and stability of the polyethylene fiber and maintaining high strength under ultraviolet irradiation.
[0031] In Comparative Example 1, alumina is directly used to load the flame retardant. On the one hand, the loading is uneven and the loading amount is small, which weakens the loading performance. On the other hand, alumina has poor dispersibility and strong agglomeration, and its compatibility with polyethylene is poor, which makes the polyethylene fiber have poor flame retardancy, low strength performance, and poor stability. Comparative Example 2 uses a primary flame retardant composite for melt spinning, omitting the crosslinking step with epoxidized guar gum. The strength stability and flame retardant stability of the polyethylene fiber prepared are poor, and the strength and flame retardancy are reduced to a certain extent, shortening the service life of the polyethylene fiber.
[0032] Unless otherwise specified, all ratios and percentages described in the present invention are by mass ratios and percentages are by mass percentages.
[0033] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing polyethylene flame-retardant fiber, characterized in that: The preparation method includes the steps of preparing an aluminum oxide compound, preparing a primary flame retardant compound, preparing a functional flame retardant compound, and mixing materials; The step of preparing the alumina composite is to place the alumina in a muffle furnace for calcination, and after the calcination is completed, wait for the alumina to naturally cool to room temperature, put it into an ethanol solution, add polyvinyl pyrrolidone, raise the temperature to 38-42°C and stir for 27-33 minutes, add vinyl tri(β-methoxyethoxy)silane and vinyl trimethoxysilane, raise the temperature to 65-70°C at a rate of 1.4-1.6°C / min, and stir for 4.8-5.2 hours. After the stirring is completed, filter and wash, then add it to N, N-dimethylformamide, add 4-mercaptoaniline, stir evenly, add benzoin dimethyl ether for ultrasonic dispersion, and after the ultrasonic dispersion is completed, perform ultraviolet irradiation for 1.4-1.6 hours at an ultraviolet wavelength of 253-264nm. After the irradiation is completed, filter, wash, and dry to obtain the alumina composite; In the step of preparing the functional flame retardant composite, the primary flame retardant composite is placed in an ethanol solution, chitosan is added and stirred, after stirring evenly, epoxidized guar gum is added, the temperature is raised to 50-54°C, and the reaction is stirred at 196-205rpm for 4.8-5.2h. After the reaction is completed, the composite is filtered and washed, and freeze-dried. The freezing temperature is -30 to -26°C, the freezing time is 11.6-12.4h, and the composite is naturally restored to room temperature to obtain the functional flame retardant composite.
2. The method for preparing a polyethylene flame-retardant fiber according to claim 1, characterized in that: In the step of preparing the alumina composite, the calcination is carried out by heating the temperature to 316-327°C at a rate of 5.5-6.5°C / min and calcining for 3.8-4.2h; The ultrasonic dispersion has an ultrasonic time of 24-26 min, an ultrasonic power of 115-124 W, and an ultrasonic frequency of 30-34 kHz.
3. The method for preparing a polyethylene flame-retardant fiber according to claim 1, characterized in that: In the step of preparing the alumina composite, the mass ratio of the alumina, ethanol solution, polyvinyl pyrrolidone, vinyl tri(β-methoxyethoxy)silane, vinyl trimethoxysilane, N,N-dimethylformamide, 4-mercaptoaniline, and benzoin dimethyl ether is 15.5-16.0:117-123:1.4-1.6:0.8-1.2:0.5-0.7:490-510:17.7-18.0:1.5-1.7; The mass concentration of the ethanol solution is 28-31%.
4. The method for preparing a polyethylene flame-retardant fiber according to claim 1, characterized in that: The steps of preparing the primary flame retardant composite are as follows: placing phosphorus oxychloride in dichloroethane, stirring evenly, and obtaining a flame retardant liquid; placing an aluminum oxide composite in dichloroethane, stirring evenly, and then dripping the flame retardant liquid, with the dripping rate controlled to be 0.4-0.6 g / min; after the dripping is completed, raising the temperature to 54-58° C., keeping the temperature and stirring for 4.8-5.2 hours, cooling to room temperature, filtering, washing, and drying to obtain the primary flame retardant composite.
5. The method for preparing a polyethylene flame-retardant fiber according to claim 1, characterized in that: In the step of preparing the primary flame retardant composite, the mass ratio of phosphorus oxychloride to ethylene dichloride is 7.7-7.7:95-105; The mass ratio of the aluminum oxide complex, ethylene dichloride and flame retardant liquid is 5.4-5.8:245-255:19.6-20.
5.
6. The method for preparing a polyethylene flame-retardant fiber according to claim 1, characterized in that: The step of preparing the functional flame retardant composite is as follows: the mass ratio of the primary flame retardant composite, the ethanol solution, the chitosan, and the epoxidized polyol is 6.1-6.4:195-205:1.6-2.0:2.2-2.5; The mass concentration of the ethanol solution is 58-62%.
7. The method for preparing a polyethylene flame-retardant fiber according to claim 1, characterized in that: In the step of preparing the functional flame retardant composite, the preparation method of the epoxidized guar gum is as follows: placing the guar gum in an ethanol solution, stirring evenly, adding sodium alginate and γ-glycidyloxypropyltriethoxysilane, raising the temperature to 60-64° C., keeping the temperature and stirring for 3.4-3.6 hours, filtering, washing and drying after the stirring is completed to obtain the epoxidized guar gum; The mass ratio of the guar gum, ethanol solution, sodium alginate and γ-glycidyloxypropyltriethoxysilane is 3.3-3.7:48-52:1.0-1.2:0.4-0.6; The mass concentration of the ethanol solution is 32-38%.
8. The method for preparing a polyethylene flame-retardant fiber according to claim 1, characterized in that: The mixing step comprises mixing ultra-high molecular weight polyethylene, medium molecular weight polyethylene, low molecular weight polyethylene, functional flame retardant compound, antioxidant 1010, oxidized polyethylene wax, oleic acid amide and sodium dodecylbenzene sulfonate, with a stirring speed of 864-875 rpm and a stirring time of 18-22 min. After the stirring, the mixture is put into a twin-screw extruder for melt spinning at a spinning temperature of 248-252° C., and then three-stage drawing is performed, wherein the first-stage drawing temperature is 98-103° C. and the drawing ratio is 4.7-5.3 times, the second-stage drawing temperature is 115-120° C. and the drawing ratio is 3.8-4.2 times, and the third-stage drawing temperature is 125-130° C. and the drawing ratio is 2.4-2.6 times, so as to obtain polyethylene flame retardant fiber.
9. The method for preparing a polyethylene flame-retardant fiber according to claim 8, characterized in that: The mass ratio of the ultra-high molecular weight polyethylene, medium molecular weight polyethylene, low molecular weight polyethylene, functional flame retardant compound, antioxidant 1010, oxidized polyethylene wax, oleic acid amide and sodium dodecylbenzene sulfonate is 15.8-16.2:58.7-60.5:12.6-13.4:3.6-4.0:1.0-1.4:0.8-1.2:0.7-1.3:0.5-0.8; The viscosity average molecular weight of the ultra-high molecular weight polyethylene is 2.24-2.26 million, the viscosity average molecular weight of the medium molecular weight polyethylene is 255,000-260,000, and the viscosity average molecular weight of the low molecular weight polyethylene is 5700-5900.
10. The polyethylene flame retardant fiber obtained according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Antibacterial flame-retardant ultra-high molecular weight polyethylene fiber and preparation method thereof
CN114086272A